Nghiên cứu so sánh cấu trúc, độ bền của cluster silic pha tạp sắt dạng trung hòa và cation, SinFe0/+ (n = 8-12), bằng phương pháp phiếm hàm mật độ - Phi, Nguyễn Duy; Trung, Nguyễn Tiến; Trí, Trần Ngọc; Thạch, Phạm Ngọc; Lan, Nguyễn Thị; Ngân, Vũ Thị (Vietnam Journal of Chemistry, 2016)
The geometries and stabilities of neutral and cationic Fe-doped silicon clusters SinFe0/+ (n = 8-12) have been investigated by using density functional theory at the B3P86/6-311+G(d) level of theory. The most stable isomers of the neutral SinFe clusters adopt high-symmetrical structure where the Fe atom binds with all of the Si atoms of the cluster. The lowest-lying isomers of the cationic clusters have different structures from the neutral, and adopt lower coordination numbers. For exohedral structures, the neutrals favor low spin states, while the cation clusters favor higher spin states. However, the endohedral structures of both neutral and cation become more stable in the lowest spin state. The endohedral cage structure appeared at n = 10 for neutral and at n = 11 for cationic clusters. The analysis of average binding energy, second order difference of energy and HOMO-LUMO gap for both series of clusters found that the cationic clusters are more stable than the corresponding neutral. The Si12Fe0/+ cluster is found to be the most stable cluster in both series. Keywords. Density functional theory, B3P86, Fe-doped silicon cluster, structure, stability